Kinetics of cone specific G-protein signaling in avian photoreceptor cells - Yee, Chad; Görtemaker, Katharina; Wellpott, Rieke; Koch, Karl-Wilhelm (Frontiers in Molecular Neuroscience, 2023)
Cone photoreceptor cells of night-migratory songbirds seem to process the primary steps of two different senses, vision and magnetoreception. The molecular basis of phototransduction is a prototypical G protein-coupled receptor pathway starting with the photoexcitation of rhodopsin or cone opsin thereby activating a heterotrimeric G protein named transducin. This interaction is well understood in vertebrate rod cells, but parameter describing protein-protein interactions of cone specific proteins are rare and not available for migratory birds. European robin is a model organism studying the orientation of birds in the earth magnetic field. Recent findings showed a link between the putative magnetoreceptor cryptochrome 4a and the cone specific G-protein of European robin. In the present work, we investigated the interaction of European robin cone specific G protein and cytoplasmic regions of long wavelength opsin. We identified the second loop in opsin connecting transmembrane regions three and four as a critical binding interface. Surface plasmon resonance studies using a synthetic peptide representing the second cytoplasmic loop and purified G protein α-subunit showed a high affinity interaction with a KD value of 21 nM. Truncation of the G protein α-subunit at the C-terminus by six amino acids slightly decreased the affinity. Our results suggest that binding of the G protein to cryptochrome can compete with the interaction of G protein and non-photoexcited long wavelength opsin. Thus, the parallel presence of two different sensory pathways in bird cone photoreceptors is reasonable under dark-adapted conditions or during illumination with short wavelengths.